Vascular flora and vegetation of Santa Rosa wetland (Chancay, Lima) - Ramirez, Dámaso W. (2010)
The present work shows the results of flora and vegetation study made between 2007 and 2009 on Santa Rosa wetland (Chancay - Lima). The vascular flora was composed for 66 species, grouped on 57 genus and 26 families. The Poaceae (16), Cyperaceae (6) and Asteraceae (6) are the more diverse families and represent the 42% of the flora. A comparison between the principal wetlands of Lima shows that Santa Rosa has more plant species (Pantanos de Villa (65), Paraíso (26) and Medio Mundo (16)). The analysis of floristic similarity between those localities shows that Santa Rosa is more similar to Pantanos de Villa (Lima) than the other localities. Using a Correspondence Analysis (CA), it was possible to recognize just three kinds of plant communities: a) Floating aquatic plants community, b) Totoral with associated species and c) Mixed Vega. It is considered that the changes on the plant community structure and the quantity of invasive species are indicators of the anthropic impact on the area. Human impact sources were identified and agriculture is considered the most important menace of this ecosystem.